PENGARUH KEMUDAHAN AKSES TERHADAP NIAT MELAKUKAN PINJAMAN PADA PEER TO PEER LENDING - Gwenn L. L. Pattinama (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The development of loans on the P2P lending platform is currently experiencing very rapid progress. Many requests for these loans are received from various groups, from young people to old people. P2P lending is a technology-based loan service. Many things can affect the development of loans in P2P lending. One of them is making the P2P lending platform more accessible to consumers. The purpose of this study was to determine whether ease of access affects the intention to continue borrowing in P2P lending. The sampling technique used was purposive sampling. The type of data used was a survey. The number of samples collected was 70 micro-businesses in Sirimau District, Ambon City. The method used was a quantitative method. The instrument tests used were validity tests and reliability tests. The regression analysis used was simple regression, coefficient of determination, and hypothesis testing, namely the t-test. The results of this study indicate that the accessibility variable has a positive and significant effect on refinancing intentions in P2P lending.